Pengaturan Pemidanaan Penyalahgunaan Artificial Intelligence dalam Penyebaran Hoax Politik Melalui Media Sosial - Laode Rachman Pratama; Nynda Fatmawati Octarina (Indo Publishing, 2026)
This study analyzes the criminal law regulations of the misuse of Artificial Intelligence (AI) in the spread of political hoaxes through social media in Indonesia, against the backdrop of the increasing threat of disinformation mediated by advanced technologies such as deepfakes and generative AI. The results reveal a legal gap in Indonesia's criminal law framework. Although the ITE Law (Article 28) is capable of prosecuting perpetrators of conventional hoax spreaders, existing regulations struggle to criminalize AI as an instrument of crime, particularly in determining criminal liability and malicious intent (mens rea) because the legal system still centers on human legal subjects.The main challenge for law enforcement lies in the complexity of evidence, where authorities struggle to verify the authenticity of AI-based hoax content and identify the human agency (programmer or end user) behind the hoax's production. Limited digital forensic expertise among law enforcement agencies further hampers the investigation process. To address this, the development of adaptive laws is recommended, namely: (1) revising the ITE Law to define the misuse of AI as a tool of crime, (2) establishing a legal obligation for social media platforms to label AI-generated content, and (3) improving the technical capacity of law enforcement. These developments aim to strengthen the effectiveness of criminalization, ensure legal certainty, and protect political integrity from the impact of AI-based disinformation.